THE ROLE OF WORK MOTIVATION IN MEDIATING THE EFFECT OF THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Andi Prayogi, Muhammad; Yani, Irma (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to determine the effect of the work environment on employee performance mediated by work motivation at the Dinas Pemuda dan Olahraga of North Sumatra province. The method used in this research is using a quantitative descriptive approach. The population in this study were general employees in the youth and sports department of the province of North Sumatra with a total population of 107 and in this study the sample obtained was 52 respondents. The results of this study indicate that the work environment has a positive but not significant effect on. employee performance, work environment has a positive and significant effect on work motivation, work motivation has a positive and insignificant effect on employee performance, work environment on employee performance is mediated by work motivation.